Blue-green adjustable luminescent perovskite quantum dot borosilicate glass material as well as preparation method and application thereof

By doping CsPb(Cl/Br)3 perovskite quantum dots in borosilicate glass and preparing them by autologous crystallization method, the problem of poor environmental stability of traditional perovskite quantum dot materials is solved, and high stability is achieved And blue-green tunable luminescence perovskite quantum dot borosilicate glass material, suitable for the optoelectronics field.

CN119241081AActive Publication Date: 2025-01-03CHINA JILIANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411369852.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Traditional perovskite quantum dot materials are susceptible to environmental factors, resulting in poor environmental stability, limiting their practical application in the field of photoelectricity.

Method used

By doping CsPb(Cl/Br)3 perovskite quantum dots into borosilicate glass, the environmental stability of the material is improved, and blue-green adjustable luminescent calcium is prepared in borate glass by autologous crystallization method. Titanium ore quantum dot borosilicate glass material avoids further annealing and heat treatment, is simple to operate, is low in cost and is low in energy consumption.

Benefits of technology

It significantly improves the environmental stability and temperature resilience of perovskite quantum dot materials, and achieves blue-green adjustable luminescence from 414nm to 522nm. It is suitable for LED, laser illumination and optical sensing, maintaining the photoelectric performance in harsh environments. stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241081A_ABST
    Figure CN119241081A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid luminescent materials, in particular to a blue-green adjustable luminescent perovskite quantum dot borosilicate glass material as well as a preparation method and application thereof. The CsPb (Cl / Br) 3 perovskite quantum dots are doped into the borosilicate glass, so that the environmental stability of the blue-green adjustable luminescent perovskite quantum dot borosilicate glass material is improved, and the photoelectric property of the perovskite quantum dots is effectively exerted. Moreover, the blue-green adjustable luminescent perovskite quantum dot borosilicate glass material provided by the invention has excellent temperature resilience, and when the temperature is raised from room temperature to 280 DEG C and then is reduced to room temperature, the luminescent intensity during cooling is equivalent to the luminescent intensity during the temperature raising process at the same temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid luminescent materials, and in particular to a blue-green tunable luminescent perovskite quantum dot borosilicate glass material and a preparation method and application thereof. Background Art

[0002] Perovskite quantum dots refer to semiconductor nanoparticles with a perovskite crystal structure (cubic crystal structure with the structural formula ABX3). These nanoparticles exhibit quantum confinement effects, that is, their optical and electrical properties are affected by their size and shape. Perovskite quantum dot materials have broad application prospects in the fields of LED, laser lighting and optical sensing due to their excellent optoelectronic properties such as high fluorescence quantum yield, adjustable band gap and narrow emission band gap. However, traditional perovskite quantum dot materials are easily degraded by environmental factors (such as humidity, heat and oxygen), and face the problem of poor environmental stability in practical applications, which seriously limits their practical application in the optoelectronic field. Summary of the invention

[0003] In view of this, the object of the present invention is to provide a blue-green tunable luminescent perovskite quantum dot borosilicate glass material and its preparation method and application. The perovskite quantum dots of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material provided by the present invention have good environmental stability.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The invention provides a blue-green tunable luminescent perovskite quantum dot borosilicate glass material, which has a chemical composition, measured by the amount of substances, of 52-64 parts of H3BO3, 26-32 parts of SiO2, 4-10 parts of ZnO, 10-17 parts of Na2CO3, 5-10 parts of Cs2CO3, 15-24 parts of PbX2 and 6-16 parts of NaX, wherein X is Cl and / or Br.

[0006] Preferably, when X is Cl and Br, the molar ratio of PbCl2 and PbBr2 is 0-19:0-19; the molar ratio of NaCl2 and NaBr2 is 0-11:0-11.

[0007] Preferably, the chemical composition of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material includes 52 to 64 parts of H3BO3, 26 to 32 parts of SiO2, 4 to 10 parts of ZnO, 10 to 17 parts of Na2CO3, 8 parts of Cs2CO3, 19 parts of PbX2 and 11 parts of NaX, in terms of the amount of substances, wherein X is Cl and / or Br.

[0008] The present invention provides a method for preparing the blue-green tunable luminescent perovskite quantum dot borosilicate glass material described in the above technical solution, comprising the following steps:

[0009] According to the chemical composition of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material, the prepared raw materials are mixed and then melted to obtain a glass melt;

[0010] The glass melt is cast and then cooled to obtain the blue-green tunable luminescent perovskite quantum dot borosilicate glass material;

[0011] Preferably, the melting temperature is 1000-1200° C. and the melting time is 10-30 min.

[0012] Preferably, the mixing includes grinding and mixing; the particle size of the mixture obtained by grinding and mixing is 1 to 5 μm.

[0013] Preferably, the casting time is less than 6 minutes.

[0014] Preferably, the casting molding comprises: pouring the glass melt onto a preheated preheating plate and letting it stand.

[0015] Preferably, the temperature of the preheated preheating plate is 300-450° C.; and the pouring time is less than 1 min.

[0016] The present invention provides the application of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material described in the above technical scheme or the blue-green tunable luminescent perovskite quantum dot borosilicate glass material prepared by the preparation method described in the above technical scheme in LED, laser lighting or optical sensing.

[0017] The present invention provides a blue-green tunable luminescent perovskite quantum dot borosilicate glass material, which, in terms of the amount of substances, has a chemical composition comprising: 52-64 parts of H3BO3, 26-32 parts of SiO2, 4-10 parts of ZnO, 10-17 parts of Na2CO3, 5-10 parts of Cs2CO3, 15-24 parts of PbX2 and 6-16 parts of NaX, wherein X is Cl and / or Br. The present invention not only improves the environmental stability of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material by doping CsPb(Cl / Br)3 perovskite quantum dots into borosilicate glass, but also effectively exerts the photoelectric properties of the perovskite quantum dots. Moreover, the blue-green tunable luminescent perovskite quantum dot borosilicate glass material provided by the present invention has excellent temperature resilience, and when it is heated from room temperature to 280°C and then cooled to room temperature, the luminous intensity during cooling is equivalent to the luminous intensity during heating at the same temperature.

[0018] Furthermore, the present invention obtains a perovskite quantum dot borosilicate glass material with blue-green tunable luminescence from 414 to 522 nm by adjusting the ratio of Cl and Br in the blue-green tunable luminescent perovskite quantum dot borosilicate glass material.

[0019] The method for preparing the blue-green tunable luminescent perovskite quantum dot borosilicate glass material described in the above technical solution provided by the present invention successfully prepares the blue-green tunable luminescent perovskite quantum dot borosilicate glass material in borate glass by a self-crystallization method. The preparation process does not require further annealing and heat treatment, is simple to operate, has low cost, low energy consumption, low environmental pollution, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 XRD diffraction pattern of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material prepared in Examples 1 to 5;

[0021] Figure 2 Transmission electron microscope images of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material prepared in Examples 1 to 5;

[0022] Figure 3 This is a particle size distribution diagram of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material prepared in Example 5;

[0023] Figure 4 The emission spectra of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material prepared in Examples 1 to 5;

[0024] Figure 5 This is an absorption spectrum of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material prepared in Examples 1 to 5;

[0025] Figure 6 This is a temperature-dependent luminescence intensity variation diagram of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material prepared in Example 5. DETAILED DESCRIPTION

[0026] The invention provides a blue-green tunable luminescent perovskite quantum dot borosilicate glass material, which has a chemical composition, measured by the amount of substances, of 52-64 parts of H3BO3, 26-32 parts of SiO2, 4-10 parts of ZnO, 10-17 parts of Na2CO3, 5-10 parts of Cs2CO3, 15-24 parts of PbX2 and 6-16 parts of NaX, wherein X is Cl and / or Br.

[0027] Measured by the amount of substance, the chemical composition of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material provided by the present invention includes 52 to 64 parts of H3BO3. In a specific embodiment, the amount of H3BO3 can be 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, 62 parts or 64 parts.

[0028] Based on the molar fraction of the H3BO3, the chemical composition of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material provided by the present invention includes 26 to 32 parts of SiO2. In a specific embodiment, the molar fraction of the SiO2 can be 26, 27, 28, 29, 30, 31 or 32 parts.

[0029] Based on the molar fraction of the H3BO3, the chemical composition of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material provided by the present invention includes 4 to 10 parts of ZnO. In a specific embodiment, the molar fraction of the ZnO can be 4, 5, 6, 7, 8, 9 or 10 parts.

[0030] Based on the molar fraction of the H3BO3, the chemical composition of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material provided by the present invention includes 10 to 17 parts of Na2CO3. In a specific embodiment, the molar fraction of the Na2CO3 can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts or 17 parts.

[0031] Based on the molar fraction of the H3BO3, the chemical composition of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material provided by the present invention includes 5 to 10 parts of Cs2CO3. In a specific embodiment, the molar fraction of the Cs2CO3 can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts.

[0032] Based on the molar fraction of the H3BO3, the chemical composition of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material provided by the present invention includes 15 to 24 parts of PbX2. In a specific embodiment, the molar fraction of the PbBr2 can be 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts or 24 parts. In the present invention, when X is Cl and Br, the molar ratio of PbCl2 and PbBr2 can be 0-19:0-19. In a specific embodiment, the molar ratio of PbCl2 and PbBr2 can be 0:19, 1:18, 2:17, 3:16, 4:15, 5:14, 6.33:12.67, 7:12, 8:11, 9:10, 9.5:9.5, 11:8, 12:7, 12.67:6.33, 15:4, 17:2 or 19:0.

[0033] Based on the amount of H3BO3, the chemical composition of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material provided by the present invention includes 6 to 16 parts of NaX. In a specific embodiment, the amount of PbI2 can be 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or 16 parts. In the present invention, when X is Cl and Br, the molar ratio of NaCl2 and NaBr2 can be 0 to 11: 0 to 11. In a specific embodiment, the molar ratio of NaCl2 and NaBr2 can be 0: 11, 1: 10, 2: 9, 3.67: 7.33, 5.5: 5.5, 7.33: 3.67, 9: 2, 10: 1 or 11: 0.

[0034] In the present invention, the chemical composition of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material may include 52 to 64 parts of H3BO3, 26 to 32 parts of SiO2, 4 to 10 parts of ZnO, 10 to 17 parts of Na2CO3, 8 parts of Cs2CO3, 19 parts of PbX2 and 11 parts of NaX, calculated by the amount of substances.

[0035] The present invention provides a method for preparing the blue-green tunable luminescent perovskite quantum dot borosilicate glass material described in the above technical solution, comprising the following steps:

[0036] According to the chemical composition of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material, the prepared raw materials are mixed and then melted to obtain a glass melt;

[0037] The glass melt is cast and then cooled to obtain the blue-green tunable luminescent perovskite quantum dot borosilicate glass material.

[0038] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0039] According to the chemical composition of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material, the present invention mixes the raw materials for preparation and then melts them to obtain a glass melt. In a specific embodiment, the optional types and the amount of the raw materials for preparation can be the same as the types and the amount of the chemical composition of the prepared blue-green tunable luminescent perovskite quantum dot borosilicate glass material, and will not be repeated here.

[0040] In the present invention, the melting temperature may be 1000-1200°C. In a specific embodiment, the melting temperature may be 1000°C, 1050°C, 1100°C, 1150°C or 1200°C. The melting time may be 10-30 minutes. In a specific embodiment, the melting time may be 10 minutes, 15 minutes, 20 minutes, 25 minutes or 30 minutes. In a specific embodiment, the mixing may include grinding and mixing. The present invention has no special restrictions on the grinding and mixing time and the particle size of the mixture obtained by grinding and mixing, as long as the raw materials can be completely mixed. In a specific embodiment, the particle size of the mixture obtained by grinding and mixing may be 1-5 μm, and may be 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.

[0041] The present invention can place the mixed material obtained by mixing in a crucible, and place the crucible in a muffle furnace for melting. In a specific embodiment, the crucible can be an alumina crucible; and the muffle furnace can be a silicon carbide muffle furnace.

[0042] After obtaining the glass melt, the present invention casts the glass melt and then cools it to obtain the blue-green tunable luminescent perovskite quantum dot borosilicate glass material.

[0043] In the present invention, the casting time may be less than 6 min. In a specific embodiment, the casting time may be 5.2 min, 5.3 min, 5.4 min, 5.5 min, 5.6 min, 5.7 min or 5.8 min.

[0044] In the present invention, the casting molding may include: pouring the molten glass onto a preheated preheating plate and letting it stand. In the present invention, the temperature of the preheated preheating plate may be 300-450°C. In a specific embodiment, the temperature of the preheated preheating plate may be 300°C, 320°C, 350°C, 370°C, 400°C or 450°C; the casting time may be <1min. The present invention pours the molten glass onto the preheated preheating plate quickly (<1min) to prevent the molten glass from cooling and solidifying due to a slow casting speed and being unable to be poured out.

[0045] In the present invention, the temperature of the standing still can be the same as the temperature of the preheating plate after preheating, which will not be described in detail. The present invention stands still on the preheating plate after pouring to prevent the glass melt from breaking due to a rapid drop in temperature.

[0046] In the present invention, the cooling may include natural cooling; the final temperature of the cooling may be room temperature. The present invention uses a self-crystallization method, which does not require further annealing and heat treatment, is simple to operate, and reduces preparation energy consumption.

[0047] The present invention provides the application of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material described in the above technical solution or the blue-green tunable luminescent perovskite quantum dot borosilicate glass material prepared by the preparation method described in the above technical solution in display, lighting or optical communication. The blue-green tunable luminescent perovskite quantum dot borosilicate glass material provided by the present invention has good environmental stability and excellent temperature resilience, and can be tunable in blue-green from 414nm to 522nm. When applied to LED, laser lighting or optical sensing, the photoelectric performance can remain stable in harsh environments.

[0048] In order to further illustrate the present invention, a blue-green tunable luminescent perovskite quantum dot borosilicate glass material provided by the present invention and its preparation method and application are described in detail below in combination with embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0049] Example 1

[0050] Calculated by amount, 58 parts of H3BO3, 29 parts of SiO2, 7 parts of ZnO, 15 parts of Na2CO3, 8 parts of Cs2CO3, 19 parts of PbCl2 and 11 parts of NaCl were ground and mixed to a particle size of 2 μm, loaded into an alumina crucible, covered and placed in a muffle furnace, and melted at 1100°C for 15 minutes to obtain a glass melt.

[0051] The obtained glass melt was poured onto a preheating plate preheated to 400° C. within 1 minute, allowed to stand for 5 minutes, and then naturally cooled to room temperature to obtain a blue-green tunable luminescent perovskite quantum dot borosilicate glass material (denoted as PG1).

[0052] Example 2

[0053] A blue-green tunable luminescent perovskite quantum dot borosilicate glass material (denoted as PG2) was prepared according to the preparation method in Example 1. The only difference from Example 1 is that, in terms of the amount of substances, the preparation raw materials are: 58 parts of H3BO3, 29 parts of SiO2, 7 parts of ZnO, 15 parts of Na2CO3, 8 parts of Cs2CO3, 7 parts of PbBr2, 12 parts of PbCl2, 2 parts of NaBr and 11 parts of NaCl.

[0054] Example 3

[0055] A blue-green tunable luminescent perovskite quantum dot borosilicate glass material (denoted as PG3) was prepared according to the preparation method in Example 1. The only difference from Example 1 is that, in terms of the amount of substances, the preparation raw materials are: 58 parts of H3BO3, 29 parts of SiO2, 7 parts of ZnO, 15 parts of Na2CO3, 8 parts of Cs2CO3, 9.5 parts of PbBr2, 9.5 parts of PbCl2, 5.5 parts of NaBr and 5.5 parts of NaCl.

[0056] Example 4

[0057] A blue-green tunable luminescent perovskite quantum dot borosilicate glass material (denoted as PG4) was prepared according to the preparation method in Example 1. The only difference from Example 1 is that, in terms of the amount of substances, the preparation raw materials are: 58 parts of H3BO3, 29 parts of SiO2, 7 parts of ZnO, 15 parts of Na2CO3, 8 parts of Cs2CO3, 12 parts of PbBr2, 7 parts of PbCl2, 9 parts of NaBr and 2 parts of NaCl.

[0058] Example 5

[0059] A blue-green tunable luminescent perovskite quantum dot borosilicate glass material (denoted as PG5) was prepared according to the preparation method in Example 1. The only difference from Example 1 is that, in terms of the amount of substances, the preparation raw materials are: 58 parts of H3BO3, 29 parts of SiO2, 7 parts of ZnO, 15 parts of Na2CO3, 8 parts of Cs2CO3, 19 parts of PbBr2 and 11 parts of NaBr.

[0060] Figure 1 The XRD diffraction pattern of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material prepared in Examples 1 to 5. Figure 1 It can be seen that the blue-green tunable luminescent perovskite quantum dot borosilicate glass materials prepared in Examples 1 to 5 all have XRD diffraction peaks corresponding to CsPbCl3 perovskite quantum dots, and their PDF card number is 75-0408 (the CsPbBr3 standard PDF card and the CsPbCl3 standard PDF card are only different in the position of the diffraction peak, so CsPb(Cl / Br)3, CsPbBr3 and CsPbCl3 can all correspond to the CsPbCl3 standard PDF card, so only the CsPbCl3 standard PDF card is compared). As the Br element content in the glass material increases, the diffraction peak gradually shifts to a small angle. This is because the radius of the Br atom is larger than that of the Cl atom. Adding the Br element increases the size of the CsPb(Cl / Br)3 perovskite quantum dots, so the XRD diffraction peak shifts to a small angle.

[0061] Figure 2 This is a transmission electron microscope image of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material prepared in Example 5. Figure 3 This is a particle size distribution diagram of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material prepared in Example 5. Figure 2 and Figure 3 It can be seen that many spherical particles can be observed in the transmission electron microscope image of PG5. These spherical particles are CsPb(Cl / Br)3 perovskite quantum dots with an average diameter of about 3.3nm.

[0062] Figure 4 The emission spectra of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material prepared in Examples 1 to 5 are shown in FIG. Figure 4 It can be seen that by adjusting the ratio of Cl and Br in the blue-green tunable luminescent perovskite quantum dot borosilicate glass material, the blue-green tunable luminescence of the glass material from 414nm to 522nm can be achieved.

[0063] Figure 5 The absorption spectra of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material prepared in Examples 1 to 5 are shown in FIG. Figure 5 It can be seen that the absorption spectra of the blue-green tunable luminescent perovskite quantum dot borosilicate glass materials prepared in Examples 1 to 5 also have the characteristic of being blue-green tunable.

[0064] Figure 6 This is a temperature-dependent luminescence intensity variation diagram of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material prepared in Example 6. Figure 5 It can be seen that the luminescence intensity of PG5 gradually decreases. This is because the non-radiative transition probability increases with temperature, which reduces the luminescence intensity. When the temperature gradually decreases from high temperature to room temperature, the luminescence intensity of the PG5 sample almost returns to its original value, indicating that the PG5 sample has excellent temperature resilience.

[0065] Comparative Example 1

[0066] Traditional colloidal perovskite quantum dots prepared according to the literature (Daqin Chen, Shuo Yuan, Jiangkun Chen, et al. Robust CsPbX3 (X = Cl, Br, and I) perovskite quantum dot embedded glasses: nanocrystallization, improved stability and visible full-spectral tunable. [J] Journal of Materials Chemistry C, 2018, 6, 12864).

[0067] After testing, the blue-green tunable luminescent perovskite quantum dot borosilicate glass material provided in Examples 1 to 5 still maintains a luminescence intensity of about 30% of the original value when heated above 100°C, and has good thermal stability; while the colloidal perovskite quantum dots prepared in Comparative Example 1 have a luminescence intensity of only about 8% of the original value when heated to 100°C, and have poor thermal stability.

[0068] In summary, the blue-green tunable luminescent perovskite quantum dot borosilicate glass material provided by the present invention has excellent environmental stability. Moreover, by changing the ratio of Cl and Br in the borosilicate glass and self-crystallization, CsPb(Cl / Br)3 perovskite quantum dots with blue-green tunable luminescence and good temperature resilience can be prepared in the borosilicate glass.

[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A blue-green tunable luminescent perovskite quantum dot borosilicate glass material, the chemical composition of which, in terms of molar fraction, comprises: H3BO3 52-64 parts, SiO2 26-32 parts, ZnO 4-10 parts, Na2CO3 10-17 parts, Cs2CO3 5-10 parts, PbX2 15-24 parts and NaX 6-16 parts, wherein X is Cl and / or Br.

2. The blue-green tunable luminescent perovskite quantum dot borosilicate glass material according to claim 1, characterized in that: When X is Cl and Br, the molar ratio of PbCl2 to PbBr2 is 0-19:0-19; the molar ratio of NaCl2 to NaBr2 is 0-11:0-11.

3. The blue-green tunable luminescent perovskite quantum dot borosilicate glass material according to claim 1 or 2, characterized in that: Calculated by the amount of substances, the chemical composition of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material includes 52 to 64 parts of H3BO3, 26 to 32 parts of SiO2, 4 to 10 parts of ZnO, 10 to 17 parts of Na2CO3, 8 parts of Cs2CO3, 19 parts of PbX2 and 11 parts of NaX.

4. The method for preparing the blue-green tunable luminescent perovskite quantum dot borosilicate glass material according to any one of claims 1 to 3, characterized in that: The following steps are involved: According to the chemical composition of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material, the prepared raw materials are mixed and then melted to obtain a glass melt; The glass melt is cast and then cooled to obtain the blue-green tunable luminescent perovskite quantum dot borosilicate glass material.

5. The preparation method according to claim 4, characterized in that: The melting temperature is 1000-1200° C. and the melting time is 10-30 minutes.

6. The preparation method according to claim 4, characterized in that: The mixing includes grinding and mixing; the particle size of the mixture obtained by grinding and mixing is 1 to 5 μm.

7. The preparation method according to claim 4, characterized in that: The pouring molding time is less than 6 minutes.

8. The preparation method according to claim 4 or 7, characterized in that: The casting molding comprises: casting the glass melt onto a preheated preheating plate and letting it stand.

9. The preparation method according to claim 8, characterized in that: The temperature of the preheated preheating plate is 300-450° C.; the pouring time is less than 1 minute.

10. Use of the blue-green tunable luminescent perovskite quantum dot borosilicate glass material according to any one of claims 1 to 3 or the blue-green tunable luminescent perovskite quantum dot borosilicate glass material prepared by the preparation method according to any one of claims 4 to 9 in LED, laser lighting or optical sensing.

Citation Information

Patent Citations

  • Perovskite quantum dot microcrystalline glass and preparation method thereof

    CN114133141A

  • Full-inorganic perovskite quantum dot composite glass and preparation method thereof

    CN115259663A

  • Method for enhancing luminescence of perovskite quantum dot glass

    CN117142763A

  • Perovskite quantum dot glass, photochromic method and application

    CN118619548A